Blending Tradition and Technology in Digital Da‘wah: Strategies and Challenges of Tuan Guru in Lombok - Lalu Ahmad Zaenuri; Muhammad Amrillah (Lembaga Bale Literasi, 2026)
In the digital era, Islamic preaching (da‘wah) has increasingly evolved through the interaction between established religious practices and modern communication technologies. This study examines Tuan Guru in Lombok who integrate digital media into their preaching strategies while maintaining traditional da‘wah practices, as well as the challenges arising from this process. Using a qualitative approach based on Interpretative Phenomenological Analysis (IPA), the study explores the experiences of seven Tuan Guru who have actively adopted digital tools in their religious outreach. While previous studies on digital da‘wah have largely focused on platforms and content strategies, this study offers new insight by highlighting the lived experiences of Tuan Guru in Lombok as they negotiate digital transformation while sustaining traditional religious authority and local cultural values. The findings reveal three main strategies through which traditional and digital preaching are combined: transforming sermon delivery, reconfiguring religious authority, and adapting local cultural values to digital contexts. At the same time, this integration is shaped by several constraints. The use of digital media for da‘wah remains limited by inadequate technological infrastructure, especially unstable internet access in many rural areas of Lombok, reducing the reach and consistency of online preaching activities. Moreover, the shift from individual preaching to team-based content production requires new forms of coordination and technical skills. Ethical concerns also emerge in maintaining the accuracy and authenticity of religious messages in fast-moving digital spaces. These findings show that Tuan Guru in Lombok must balance technological adaptation with preserving core religious values in their preaching practices.